Policy Analysis on Green Open Space Planning in Bandar Lampung City - Rein Susinda Hesty (Jurnal Arsitektur, 2023)
The formulation of sustainable green open space is influenced by various criteria, with variables whose indicators influence the creation of sustainable green open space. By identifying the chosen technique, this study intends to determine the need for green open space in Bandar Lampung City in 2024 in order to realize sustainable green open space. According to the PERMEN PU in 2008 regarding the minimum area of green open space per person, there is a requirement for green open space of 20 m2 per person. The results of the study showed that, in accordance with applicable regulations, the population of Bandar Lampung City experienced an increase in the need for green open space every year as a result of the population growth that occurred. The initial stage of the analysis is carried out on existing population data. Planning, design, and management of green open space is an integral part of improving and maintaining the resilience of the built environment in urban areas. If green open space works, it can increase resilience and facilitate the quality of the urban environment. The quality of green open space requires proper analysis. The aim is to develop policies in open space planning so that it can work as an infrastructure for its enhancement and resilience. The results show that control through direct control and administrative control mechanisms.